Художественное выражение женского образа в современной греческой прозе - Банах, Л.С. (Культура народов Причерноморья, 2004)
The aim of this article is to analyze the interpretation of the women's images in the prose of modern Greek authors Sotiris Dimitriou and Georgos Skambarthonis. The main attention is paid to the tendencies and innovations in the description of the women's state in the works of art of Greek prose making out the traditions in the interpretation of women's images.